Pengaruh Ketidakpastian Lingkungan, Sistem Informasi Akuntansi, Dan E–Commerce Terhadap Kinerja Umkm Pada Coffee Shop Di Kota Medan - Nabilla Dwi Agintha; Ebriyana Sri Rezeki Sinurat (Jurnal Riset Akuntansi dan Bisnis, 2026)
This research uses a quantitative method with an associative approach. The data were collected through questionnaires distributed to 62 coffee shop MSME actors in Medan City using a purposive sampling technique. The data were then analyzed using multiple linear regression with the help of SPSS. The results show that partially, environmental uncertainty does not have a significant effect on MSME performance, with a significance value of 0.516 0.05. Meanwhile, accounting information systems and e-commerce have a significant effect on MSME performance, with significance values of 0.013 0.05 and 0.029 0.05, respectively. Simultaneously, environmental uncertainty, accounting information systems, and e-commerce have a significant effect on MSME performance, with a significance value of 0.009 0.05. The Adjusted R Square value of 0.151 indicates that the variables in this study explain 15.1% of MSME performance. Based on these results, it can be concluded that accounting information systems and e-commerce play an important role in improving MSME performance, while environmental uncertainty does not have a significant effect..